2013
DOI: 10.1177/0020764013504561
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of insight in first-episode schizophrenia: A 5-year cohort study from India

Abstract: These findings argue that insight and explanatory models of illness are secondary to psychopathology, course and outcome. They are dependent on the trajectory of the person's illness, are not independent of the condition and call for multifaceted understanding of the issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(45 citation statements)
references
References 33 publications
0
45
0
Order By: Relevance
“…severe illness with poor outcome predicting ''poor insight'' and non-medical EMs). Nevertheless, recent investigations, which have systematically elicited prevalent EMs, have reported that good insight has also been positively associated with the number of nonmedical EMs of illness (Johnson et al, 2012(Johnson et al, , 2013. They also suggest that holding non-medical EMs, does not necessarily imply that they do not subscribe to medical EMs.…”
Section: Cross-sectional Associationsmentioning
confidence: 99%
See 4 more Smart Citations
“…severe illness with poor outcome predicting ''poor insight'' and non-medical EMs). Nevertheless, recent investigations, which have systematically elicited prevalent EMs, have reported that good insight has also been positively associated with the number of nonmedical EMs of illness (Johnson et al, 2012(Johnson et al, , 2013. They also suggest that holding non-medical EMs, does not necessarily imply that they do not subscribe to medical EMs.…”
Section: Cross-sectional Associationsmentioning
confidence: 99%
“…Many reports, which have systematically elicited EMs, have documented the presence of multiple and contradictory beliefs about illness across cultures (Kapoor, 1975;Gater et al, 1991;Lloyd et al, 1998;Joel et al, 2003;McCabe and Priebe, 2004;Saravanan et al, 2007aSaravanan et al, ,b, 2010Johnson et al, 2012Johnson et al, , 2013Johnson et al, , 2014. EMs are usually a conglomeration of emic and etic approaches involving ethnocultural, personal and idiosyncratic beliefs and components from both within and outside culture.…”
Section: Single and Multiple Explanatory Modelsmentioning
confidence: 99%
See 3 more Smart Citations